Reproductive factors for ovarian cancer in southern Chinese women - Pasalich, Maria; Su, Dada; Binns, Colin; Lee, Andy (Korean Society of Gynecologic Oncology, 2013)
Objective: To investigate the association between reproductive factors and the risk of ovarian cancer among southern Chinese women. Methods: A hospital-based case-control study was undertaken in Guangzhou, Guangdong Province, between 2006 and 2008. A structured questionnaire was used to obtain information on parity, oral contraceptive use and other reproductive factors in a sample of 500 incident ovarian cancer patients and 500 controls (mean age, 59 years). Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using unconditional logistic regression models. Results: High parity was inversely associated with ovarian cancer, with an adjusted OR 0.43 (95% CI, 0.30 to 0.62) for women who had given birth to 3 or more children compared to women who had given no more than one birth. Ever use of oral contraceptives was also protective against ovarian cancer; adjusted OR 0.56 (95% CI, 0.40 to 0.78). No association was found for hormone replacement therapy, menopausal status, hysterectomy and family history of ovarian and/or breast cancer. Conclusion: High parity and oral contraceptive use are associated with a lower risk of ovarian cancer in southern Chinese women.